2015
DOI: 10.1007/s11661-015-3282-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Electrical Properties of Applied Amorphized and Polycrystalline Sb2S3 Thin Films

Abstract: One of the intermediate steps in the organo-colloidal synthesis of crystalline Sb 2 S 3 is a synthesis of spherical amorphous Sb 2 S 3 . In order to prove that the synthesized semiconductor can be considered an absorbing material for a solar device, the electronic and photovoltage properties of the amorphized and polycrystalline Sb 2 S 3 thin films deposited by synthesized amorphous nanoparticles were studied. Optical studies revealed that the direct band gap energy was 1.65 eV and, two direct allowed transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The optimum thickness yielding the highest efficiency and other cell parameters was found to be 100 nm. As given in our earlier paper synthesized amorphous Sb 2 S 3 film exhibit better photovoltaic performances than the crystalline Sb 2 S 3 one in photo‐electrochemical solar cell.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…The optimum thickness yielding the highest efficiency and other cell parameters was found to be 100 nm. As given in our earlier paper synthesized amorphous Sb 2 S 3 film exhibit better photovoltaic performances than the crystalline Sb 2 S 3 one in photo‐electrochemical solar cell.…”
Section: Resultsmentioning
confidence: 58%
“…Independently of the performance of the tested solar cells under 1 sun, finding low‐cost cell technology combined with understanding of utilization of low light and setting of standard conditions (1–10 W m −2 , indoors) should be some future directions concerning the research in this area . Our opinion is backed up by experiments we carried out with synthesized Sb 2 S 3 solar cells operating at low light intensity, as well as the results presented in this article.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Absorption spectroscopy revealed that the optical band-gap of the synthesized glasses and Sb 2 S 3 crystals is different with values 2.1 and 1.7 eV, respectively [17,18]. To cause absorption of the laser beam enough for heating of glasses but relatively small by crystal, we selected a CW diode laser with intermediate wavelength of 639 nm (i.e.…”
Section: Methodsmentioning
confidence: 99%